Beginning Scala 3 - A Functional and Object-Oriented Java Language (3rd Edition) - David Pollak, Vishal Layka, Andres Sacco (Apress, an imprint of Springer Nature, 2022)
Learn the latest version of Scala through simple, practical examples. This book introduces you to the Scala programming language, its object-oriented and functional programming characteristics, and then guides you through Scala constructs and libraries that allow you to assemble small components into high-performance, scalable systems. This book explores new Scala 3 language features such as Top-level declarations, Creator applications, Extension methods to add extra functionality to existing types, and Enums. You will also learn new ways to manipulate types via Union types, intersection, literal, and opaque type aliases. Additionally, you'll see how Implicits are replaced by given and using clauses. After reading this book, you will understand why Scala is judiciously used for critical business applications by leading companies such as Twitter, LinkedIn, Foursquare, the Guardian, Morgan Stanley, Credit Suisse, UBS, and HSBC - and you will be able to use it in your own projects.